2005
DOI: 10.1177/010740830502500211
|View full text |Cite
|
Sign up to set email alerts
|

Den perioperativa dialogen ur barn med sarskilda behovs perspektiv

Abstract: IntroduktionSom anestesisjuksköterska möter man barn med särskilda behov, vars mognadsålder inte motsvarar den kronologiska åldern. Barnen kan ha någon form av utvecklingshämning, eller leva under otrygga hemförhållanden (1). Rydelius (1) menar att utvecklingshämmade barn löper större risk än andra barn att utveckla oro och rädsla när felaktiga krav och förväntningar ställs på dem. Otrygga hemförhållanden kan medföra att barnens rädsla inte står i relation till ingreppets art. Alla barn kan utveckla särskilda … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The empirical research findings are derived from seven peer reviewed articles (Lindberg and Post 2005;Lindberg andPost 2006, Lindberg et al 2012;Lindberg et al 2013;Rudolfsson et al 2003a;Rudolfsson et al 2007aRudolfsson et al , 2007b. All seven studies were qualitative.…”
Section: Empirical Underpinning Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The empirical research findings are derived from seven peer reviewed articles (Lindberg and Post 2005;Lindberg andPost 2006, Lindberg et al 2012;Lindberg et al 2013;Rudolfsson et al 2003a;Rudolfsson et al 2007aRudolfsson et al , 2007b. All seven studies were qualitative.…”
Section: Empirical Underpinning Of the Studymentioning
confidence: 99%
“…Several children described their participation in the dialogue as getting to know the nurse and that a sense of togetherness is created based on the nurse anaesthetist's continuous presence. In the course of being prepared for and then being administered the anaesthetic by the same nurse the necessary knowledge becomes available to both the nurse and the child with special needs alike, thus which at the beginning may seem impossible actually turns out to be easy (Lindberg and Post 2005).…”
Section: Study IVmentioning
confidence: 99%
“…Alleviating children’s anxiety during their hospital visit is an important nursing objective, but there are also other important aims from the children’s perspective. As Lindberg and von Post ( 2005 , 2006 ) and Wennström et al ( 2008 ) have shown, by helping children prepare themselves for a procedure, children may arrive happily for the procedure and feel proud of themselves during the procedure and afterwards. These consequences could also be called children’s empowerment (Mitcheson & Cowley 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…These consequences could also be called children’s empowerment (Mitcheson & Cowley 2003 ). In these studies, empowerment was achieved through a process called Perioperative Dialogue, which is based on listening to the children and sharing information in a dialogical interaction (Lindberg & von Post, 2005 , 2006 ). Therefore, how to listen to children, also when they express themselves nonverbally, is an important question in helping children prepare for a medical procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation